Command Filter-Based Predefined Time Adaptive Control for Nonlinear Systems - Sui, Shuai; Chen, C. L. Philip; Tong, Shaocheng (IEEE transactions on automatic control, 2024)
In this article, we study the predefined-time adaptive control problem for a class of strict-feedback nonlinear systems with parametric uncertainties and disturbances. A new practical predefined time stable (PPTS) criterion is first presented as the theoretical basis of predefined time control design, and then a new nonlinear command filter is designed. Based on the established PPTS criterion and backstepping control design technique, a command filter-based predefined time adaptive backstepping control scheme is developed. The proposed control method can guarantee the control system to be PPTS and the tracking error converges to a small neighborhood around zero. Moreover, it can overcome the computational complexity and control singular problems. Finally, the simulation and comparisons are provided to verify the predefined time control performance.